2019
DOI: 10.1029/2018jg004701
|View full text |Cite
|
Sign up to set email alerts
|

Magnitudes and Drivers of Greenhouse Gas Fluxes in Floodplain Ponds During Drawdown and Inundation by the Three Gorges Reservoir

Abstract: Hydropower reservoirs are well-known emitters of greenhouse gases to the atmosphere. This is due in part to seasonal water level fluctuations that transfer terrestrial C and N from floodplains to reservoirs. Partial pressures and fluxes of the greenhouse gases CH 4 , CO 2 , and N 2 O are also a function of in situ biological C and N cycling and overall ecosystem metabolism, which varies on a diel basis within inland waters. Thus, greenhouse gas emissions in hydropower reservoirs likely vary over seasonal and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 99 publications
2
7
0
Order By: Relevance
“…We did not evaluate methane emissions from natural versus artificial ponds due to the low ( n = 23) sample size and geographical bias of artificial ponds, but this is an important future research question. Preliminary evidence suggests that artificial ponds may have higher methane fluxes, even in cases where diffusion was the only pathway measured (Gorsky et al., 2019; Ollivier et al., 2018, but see; Miller et al., 2019), and that artificial pond type matters (Grinham et al., 2018). In cases where ponds are constructed, methane emissions may be managed through morphometric design as deeper ponds often emit less methane than shallower ones (Gorsky et al., 2019; Webb et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We did not evaluate methane emissions from natural versus artificial ponds due to the low ( n = 23) sample size and geographical bias of artificial ponds, but this is an important future research question. Preliminary evidence suggests that artificial ponds may have higher methane fluxes, even in cases where diffusion was the only pathway measured (Gorsky et al., 2019; Ollivier et al., 2018, but see; Miller et al., 2019), and that artificial pond type matters (Grinham et al., 2018). In cases where ponds are constructed, methane emissions may be managed through morphometric design as deeper ponds often emit less methane than shallower ones (Gorsky et al., 2019; Webb et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, substantially larger night‐time fluxes and concentrations of CH 4 and CO 2 have been observed in arable ditches, urban ponds and channelized streams (Deng et al, 2020; Harrison et al, 2005; Natchimuthu et al, 2014) which are often attributed to variations in photosynthesis and O 2 concentrations. However, some pond and lake studies have found lower CH 4 fluxes during night‐time due to decreased wind speeds reducing gas exchange (Natchimuthu et al, 2014; Sieczko et al, 2020) and others have found no clear diel pattern in pond CH 4 or CO 2 (Miller et al, 2019), especially during winter sampling (Ollivier et al, 2019b). No diel measurements were made during our study and so we cannot be sure to what extent, if any, our annual fluxes have been under‐ or overestimated, but night‐time measurements should be a priority for future work.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified significant methane emissions in the riparian zones (Miller et al, 2019;Zhou et al, 2017). For example, Miller et al (2019) found elevated riparian methane emissions relative to the reservoir during drawdown and inundation by the Three Gorges reservoir, China.…”
Section: Spatial Patterns Of Diffusive Methane Emissionsmentioning
confidence: 99%
“…Previous studies have identified significant methane emissions in the riparian zones (Miller et al, 2019;Zhou et al, 2017). For example, Miller et al (2019) found elevated riparian methane emissions relative to the reservoir during drawdown and inundation by the Three Gorges reservoir, China. In this study, reduced methane emissions were found at the edge of the riparian zone under reservoir operation, which advanced our knowledge on methane emissions from riparian zones.…”
Section: Spatial Patterns Of Diffusive Methane Emissionsmentioning
confidence: 99%
See 1 more Smart Citation